Clinical Applications of Circulating Tumor Cells in Lung Cancer Patients by CellSearch System - Truini, Anna; Alama, Angela; Dal Bello, Maria Giovanna; Coco, Simona; Vanni, Irene; Rijavec, Erika; Genova, Carlo; Barletta, Giulia; Biello, Federica; Grossi, Francesco (Frontiers in Oncology, 2014)
Circulating tumor cells (CTCs) are cells spread from the primary tumor into the bloodstream that might represent an important biomarker in lung cancer. The prognosis of patients diagnosed with lung cancer is generally poor mainly due to late diagnosis. Recent evidences have reported that tumor aggressiveness is associated with the presence of CTCs in the blood stream; therefore several studies have focused their attention on CTC isolation, characterization and clinical significance. So far the CellSearch® system is the only approach approved by FDA for metastatic breast, prostate and colorectal cancer intended to detect CTCs of epithelial origin in whole blood and to assess prognosis. To date no specific biomarkers have been validated in lung cancer and the identification of novel tumor markers such as CTCs might highly contribute to lung cancer prognosis and management. In the present review the significance of CTC detection in lung cancer is examined through the analysis of the published studies in both non-small cell and small cell lung cancers; additionally the prognostic and the clinical role of CTC enumeration in treatment monitoring will be reported and discussed.